A clinical study of patients attending disability clinic in a tertiary care hospital of Assam, India - Baruah, Mamoni; Das, Rajiv Kumar; Vishwakarma, Daisy; Malakar, Amar Jyoti (International Journal of Research in Medical Sciences, 2019)
Background: The aim of the study was to determine the various types of congenital or acquired disorders causing permanent disability and their association with age, sex and visual acuity in patients attending disability clinic of department of ophthalmology, Jorhat medical college and hospital, Assam, from January 2018 to December 2018. Methods: A hospital-based cross-sectional study. 200 patients were enrolled in the duration of January 2018 to December 2018 and were analyzed for anomalies, etiology, sex and age at presentation. Results: Out of 200 cases analysed, 116 males and 84 females (Male: Female = 1.38:1) observed. The most common age group at presentation was 11-20 years (28.5%). 23% of cases were congenital. The most frequent ocular anomaly noted was microphthalmos (19%) followed by uveal coloboma (15%) and phthisis bulbi (14%). Conclusions: In a developing country like India, a large proportion of the childhood and adult blindness is avoidable. Action is needed to prevent blindness from vitamin A deficiency, measles, external ocular infections and chemical injuries. Specialist paediatric and optical services are required to manage cataract and glaucoma. Further work is indicated to elucidate the causes of anophthalmos, microphthalmos and coloboma. It would be useful to document the changing patterns in the causes of ocular disability to allow early action against emerging avoidable causes.